Spatial heterogeneity in Sahelian rangelands and resilience to drought and grazing - Hiernaux, Pierre H.Y. (Society of Range Management, 1996)
In studies of 25 rangeland sites selected along the S.-N. bioclimatic gradient and on the main soil types in the Gourma (Sahel, Mali), herbage cover, standing mass and botanical composition were measured in relation to seasonality of grazing and grazing intensity. When different sites were compared, variability in herbage and spatial heterogeneity were positively correlated. Spatial heterogeneity within a site increased after droughts indicating that compensation between temporal and spatial variations occurred. It was considered that drought-promoted heterogeneity may help the resilience of the vegetation by preserving spots of luxuriant growth. Grazing decreased spatial heterogeneity, however the evenness fostered by grazing did not increase vegetation sensitivity to drought. It is suggested that this was because of the convergence in plant adaptation to grazing and arid conditions.